Board Gender Diversity and Corporate Innovation: Evidence from Indonesian Family Firms - Iman Harymawan; Kendra Nismara (Journal of Accounting and Strategic Finance, 2022)
The study examines the relationship between board gender diversity and corporate innovation. A Quantitative method with OLS analysis technique, using an 868 samples data observation of Indonesia public companies listed from 2010-2019. This study found that board gender diversity has increased corporate innovation. Furthermore, using a family firm as a moderating variable, this study suggests that a family firm has weakened the positive relationship between board gender diversity and corporate innovation. Therefore, this study implies that board gender diversity is important to increase corporate innovation. In addition, this study provides that the gender diversity of CEOs in high family ownership companies can decrease corporate innovation. There are several research limitations. First, innovation, measured by R&D investment, does not particularly determine corporate innovation, as it can be measured in several other forms of intangible assets such as patents, trademarks, copyright, and franchises. Second, gender diversity association with corporate innovation was measured merely by the number of women and did not do further investigate the other factors such as their business ties, social ties, and educational background. Third, the sample only consists of companies listed on the Indonesia Stock Exchange, leaving out the other companies that did not go public.